Assessment of the inclusion of vaccination as an intervention to reduce antimicrobial resistance in AMR national action plans: a global review - Lotte van Heuvel; Saverio Caini; Michel L. A. Dückers; John Paget (BMC, 2022)
Abstract Background Vaccination can reduce antibiotic use by decreasing bacterial and viral infections and vaccines are highlighted in the WHO Global Action Plan on Antimicrobial Resistance (AMR) as an infection prevention measure to reduce AMR. Our study aimed to analyze whether WHO Member States have developed AMR national action plans that are aligned with the Global Action Plan regarding objectives on vaccination. Methods We reviewed 77 out of 90 AMR national action plans available in the WHO library that were written after publication of the Global Action Plan in 2015. Each plan was analyzed using content analysis, with a focus on vaccination and key components as defined by WHO (I. Strategic plan (e.g. goals and objectives), II. Operational plan, III. Monitoring and Evaluation plan). Results Vaccination was included in 67 of 77 AMR plans (87%) across all WHO Regions (Africa: n = 13/13, the Eastern Mediterranean: n = 15/16, Europe: n = 10/14, the Americas: n = 8/8, South-East Asia: n = 8/11, and the Western Pacific: n = 13/15). Pneumococcal and influenza vaccination were most frequently highlighted (n = 12 and n = 11). We found indications that vaccination objectives are more often included in AMR plans from lower income countries, while higher income countries more often include specific vaccines. The key WHO components of national action plans were frequently not covered (I. 47% included, II. 57%, III. 40%). In total, 33 countries (43%) included indicators (e.g. strategic objectives) to capture the role of vaccines against AMR. Conclusions While vaccination to reduce AMR is seen as an important global public health issue by WHO, there appears to be a gap in its adoption in national AMR plans. Country income levels seem to influence the progress, implementation and focus of national action plans, guided by a lack of funding and prioritization in developing countries. To better align the global response to AMR, our review suggests there is a need to update national action plans to include objectives on vaccination with more focus on specific vaccines that impact antibiotic use.